The Food & Beverage Magazine guide to restaurant success : the proven process for starting any restaurant business from scratch to success - Politz, Michael (John Wiley & Sons, Inc., 2020)
Each month, countless new restaurants open their doors as others fail. Despite continuing industry growth, many new restaurants struggle to succeed. Even established restaurants are challenged to stay open. These businesses may have great food and amazing service, yet some still face uncertain futures. Food and Beverage Magazine's Guide to Restaurant Success is written by an industry expert who has opened numerous restaurants and provided valuable restaurateur guidance in the role of a trusted consultant. This restaurant success guide provides vital information on how to protect the significant investment--sometimes ranging from $250,000 to $425,000--that's required to open a restaurant and keep it running during the first six months. Author Michael Politz started his career with an ice cream business and went on to found a number of restaurants, a frozen food distribution business, a restaurant consulting service, and a respected online magazine for the food and beverage industry. Politz shares his extensive knowledge gained through both success and failure. With his indispensable guide, you can easily double-check to make sure you're doing things right. Get guidance from a restaurant owner's handbook of what to do and not do Refer to handy tips and checklists that help you launch your business Discover insight into the triumphs of Wolfgang Puck, Bobby Flay, Emeril Lagasse, and more Gain food industry knowledge with a comprehensive restaurant how-to guide Whether you want to open a burger joint or a fine dining restaurant, this advice-filled resource will help you cover all the details that make a difference.